Staande vlnr.: Nauta, Elkerbout. Zittend vlnr.: Hofman, Amelink, Kruithof, Ruppert en Vermeulen. Uit archief CNV, port. 48 - Thomann, Anton C.,
Staande vlnr.: Nauta, Elkerbout. Zittend vlnr.: Hofman, Amelink, Kruithof, Ruppert en Vermeulen. Uit archief CNV, port. 48.